2020
DOI: 10.1097/pr9.0000000000000840
|View full text |Cite
|
Sign up to set email alerts
|

Long-term opioid therapy for chronic noncancer pain: second update of the German guidelines

Abstract: Supplemental Digital Content is Available in the Text. Neither uncritical opioid prescription nor general rejection of opioids is justified in patients with chronic noncancer pain. Responsible application requires consideration of indications, contraindications, and regular assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
11
0
15
Order By: Relevance
“…Long-term opioid treatment for CNCP is under debate globally because of the opioid epidemic in the United States (Chou et al, 2020). In European guidelines, opioids remain a treatment option in carefully selected and supervised patients with CNCP for whom established non-pharmacological therapies and nonopioid analgesics have failed or have not been tolerated (Häuser et al, 2021;Petzke et al, 2020). The health claims data which have been used to find the indication for opioid prescriptions do not allow to draw conclusions if the indication was appropriate.…”
Section: Indications For Opioid Therapymentioning
confidence: 99%
“…Long-term opioid treatment for CNCP is under debate globally because of the opioid epidemic in the United States (Chou et al, 2020). In European guidelines, opioids remain a treatment option in carefully selected and supervised patients with CNCP for whom established non-pharmacological therapies and nonopioid analgesics have failed or have not been tolerated (Häuser et al, 2021;Petzke et al, 2020). The health claims data which have been used to find the indication for opioid prescriptions do not allow to draw conclusions if the indication was appropriate.…”
Section: Indications For Opioid Therapymentioning
confidence: 99%
“…Opioids can be an important tool in the management of chronic pain. However, the experience of recent years has shown that benefit and harm in treatment of non-cancer pain can be closely related, and that opioid consumption is influenced by different factors [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid use is associated with statistically significant but small improvements in pain and physical functioning [9]. Numerous studies exist demonstrating that psychological comorbidities such as depression and anxiety are prevalent among patients with chronic non-cancer pain [3,6], and that these patients are more likely to receive long-term opioid therapy for pain [4]. A proposed reason for this phenomenon is that mental health conditions and chronic non-cancer pain are closely correlated concerning severity [5].…”
Section: Introductionmentioning
confidence: 99%
“…These include strong opioids (SO), whose consumption has increased in recent years in our setting [4,5], mostly in patients with chronic non-cancer pain (CNCP). This indication lacks evidence and has a high risk of adverse effects, leading guidelines to recommend limiting their use to very specific cases, after assessing the risk-benefit [6][7][8][9]. The risk increases with some factors such as age, comorbidity and concomitant prescription of some other drugs.…”
Section: Introductionmentioning
confidence: 99%